Habitat use and predicted range for the mainland clouded leopard Neofelis nebulosa in Peninsular Malaysia. (February 2017) - Tan, Cedric Kai Wei; Rocha, Daniel G.; Clements, Gopalasamy Reuben; Brenes-Mora, Esteban; Hedges, Laurie; Kawanishi, Kae; Mohamad, Shariff Wan; Mark Rayan, D.; Bolongon, Gilmoore; Moore, Jonathan; Wadey, Jamie; Campos-Arceiz, Ahimsa; et al.
Abstract: Ongoing deforestation in Southeast Asia is leading to increased fragmentation and reduction of habitat for the mainland clouded leopard ( Neofelis nebulosa). Using the largest detection/non-detection camera trap survey dataset known for the species throughout its range, we investigated factors affecting clouded leopard habitat use across Peninsular Malaysia. Habitat use was modelled using fine scale covariates and recently developed analytical techniques to account for spatial autocorrelation. Clouded leopard habitat use increased with increasing distance from water bodies, higher numbers of discontinuous core areas per unit area and higher elevation. In addition, clouded leopard habitat use was higher in sites with higher average forest change values. After extrapolating the predicted habitat use of clouded leopards across the whole of Peninsular Malaysia, we assessed the suitability of proposed ecological linkages, and identified other suitable forest patches not within the current Central Forest Spine. Our findings are valuable for land use planning and management, in particular, for determining the suitability of forest remnants to support populations of clouded leopard and predicting how this species will respond in human-dominated landscapes.